Preparation method of key material of fire-retardant, water-washable, moderately compatible waterborne acrylate resin coating
Patent Information
- Application Number
- CN202411755149.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-10-12
AI Technical Summary
[0012]本发明目的在于解决PCB板涂膜钻孔,存在涂膜熔融,影响钻孔精度的同时,涂膜受热熔融,导致PCB板孔中黏附膜的粘液,粘液凝固,难以去除;针对存在的弊端,本发明设计阻燃、可水洗和相容性适中的水性丙烯酸酯类树脂涂料;首先,针对受热熔融,以提高阻燃性来提升其指标,核层中采用成炭剂中间体和DOPO、3,4-环氧-1-丁烯进行自由基反应,将上述物质引入到丙烯酸酯类单体链段中,由于DOPO和对羟基苯甲醛都有苯环刚性基团,使其在钻孔过程中表面强度适中,不至于因钻孔过程高速运动而导致精度下降,且不会造成树脂膜被打断而形成过多小颗粒块而飞溅到PCB板上,降低了PCB板上的树脂膜颗粒数量;其次,3,4-环氧-1-丁烯的加入不至于使DOPO和对羟基苯甲醛所形成的树脂膜过硬而导致其脆裂;利用多孔炭层改性物、DOPO和3,4-环氧-1-丁烯参与壳层自由基反应,将上述物质引入丙烯酸酯类树脂链段中,降低丙烯酸酯类树脂的可燃性;同时糊化淀粉也增强了PCB的耐熔融性;再利用可溶性淀粉的部分羟基与苯甲酰氯的酰氯进行反应,促使其在后续糊化中不至于粘度增强过大;利用过硫酸铵作引发剂,将丙烯酰胺、十六烷基二甲基烯丙基氯化铵和N,N-亚甲基双丙烯酰胺进行自由基的溶液反应,形成可溶性丙烯酸酯类树脂,再利用碱性环境下,加速淀粉糊化,所得糊化可溶性淀粉有三个作用,a增加丙烯酸酯类树脂的熔融温度,b提高丙烯酸树脂的水溶性,c增加丙烯酸酯类树脂在加热水洗时,而发生溶胀,使其能很快从环氧树脂的PCB板进行剥离,而达到与PCB板适度相容性;针对水性问题,选择在壳层中引入亲水的丙烯酰胺、丙烯酸羟乙酯,增加壳层水洗性
[0028](1)本发明构建了核壳性的阻燃、可水洗和相容性适中的水性丙烯酸酯类树脂,在核层采用偏硬、壳层软的链段,在较高温度下,膜能在清洗中,很快从PCB板孔中脱落下来;核层中采用成炭剂中间体和DOPO、3,4-环氧-1-丁烯进行自由基反应,将上述物质引入到丙烯酸酯类单体链段中,由于DOPO和对羟基苯甲醛都有苯环刚性基团,使其在钻孔过程中不至于因钻孔过程高速运动而导致精度下降,且不会造成树脂膜被打断而形成过多小颗粒块而飞溅到PCB板上,降低了PCB板上的树脂膜颗粒数量;其次3,4-环氧-1-丁烯的加入不至于使DOPO和对羟基苯甲醛所形成的树脂膜过硬而导致其脆裂,且在pH为8时,使3,4-环氧-1-丁烯开环,引入了具有较强亲水性的二乙醇胺,利用二乙醇胺的-NH与环氧在碱性环境下开环,一方面,在丙烯酸酯类树脂链中引入了具有阻燃作用的含氮元素,另一方面,引进的羟基既增强了树脂核层的亲水性,又使树脂受热过程中,羟基脱水成炭,增强了树脂的耐熔滴和降低了PCB板上的树脂膜颗粒和增强了可水洗性;
Smart Images

Figure BDA0005166082090000131 
Figure BDA0005166082090000141 
Figure BDA0005166082090000142
Abstract
Description
[0001] This invention is a divisional application of 2024114197324. Technical Field
[0002] This invention relates to a method for preparing waterborne acrylic resin coatings, and particularly to a method for preparing flame-retardant, washable, and moderately compatible waterborne acrylic resin coatings. Background Technology
[0003] Temporary protective coatings are similar to general protective coatings, providing protection and decontamination to the surface of the object being protected. The difference lies in their short duration of action; they primarily serve a protective function during processing, transportation, or temporary storage. After processing, transportation, or storage, the coating layer needs to be removed from the protected object. Once removed, the original function and properties of the protected object should not be damaged or negatively affected. This type of coating, providing temporary protection, is also called a removable coating or a washable coating. Washable coatings, when applied to the protected object, form a tightly structured film that isolates the protected material from the external environment. Simultaneously, surface adsorption and adhesion during film formation help to absorb dirt from the protected object.
[0004] Water-washable coatings are typically removed from the surface of the protected object by soaking or rinsing with specific solvents. The coating must have a certain solubility in the solvent, which can include water, acidic or alkaline solutions, or specially formulated paint removers. They are primarily used for protecting glass and metal surfaces, or for dust collection and air purification on walls and floors.
[0005] As the cornerstone of electronic components, PCBs are crucial in their manufacturing process. Drilling accuracy is a core indicator of PCB quality, and removable coatings are key to industrial transformation and upgrading. Water-washable coatings are particularly important influencing PCB drilling accuracy. Applying removable coating to an aluminum plate, then attaching the coated aluminum plate to the PCB (copper-based or copper-clad laminate), and finally drilling can improve drilling accuracy. However, as a consumable material, the PCB needs to be cleaned after drilling to remove the coating film. Currently, the washable coatings used in PCB board processing generally have the following pain points: (a) PCB drilling requires the use of aluminum plate coatings, but traditional washable coatings have poor heat resistance and cannot withstand the heat released during drilling, causing the coating film to partially or completely melt, affecting drilling accuracy; (b) Coating splashed during drilling easily adheres to the epoxy resin through-holes of the PCB, which is difficult to remove. Residual coatings can easily cause dampness, mold, and corrosion of the circuit board, affecting the performance and lifespan of the circuit board; (c) The resin adhesion between the PCB and the aluminum plate is not moderate, with poor adhesion, poor metal (aluminum plate) compatibility, and difficulty in protection. The adhesion is too strong, making it difficult to clean.
[0006] Jia Danfeng et al. prepared a water-soluble acrylic resin using solution free radical polymerization with acrylic acid (AA), hydroxyethyl methacrylate (HEMA), and acrylamide (AM) as functional monomers, butyl acrylate and methyl methacrylate as soft and hard monomers, azobisisobutyronitrile (AIBN) as an initiator, and dimethylethanolamine as a neutralizing agent. The water-soluble acrylic resin was then compounded with an emulsion to prepare an aqueous compound resin for resin coatings. The aqueous compound resin was then compounded with fillers, water-soluble polymers, and other additives to prepare a washable temporary protective coating. The film showed an adhesion level of 2, and a 50-second demolding time after washing at 50°C, indicating good washability. However, this technique did not consider the problem of the temporary coating film bonding to metal materials when heated during use, leading to film melting and difficulty in cleaning, nor did it study core indicators such as PCB drilling accuracy.
[0007] Invention patent CN202210702763.5 relates to using polyvinyl alcohol (PVA) resin as the main resin to improve the flexibility of the coating film; using polyether-modified acrylic resin as a modifying resin to improve the adhesion of the coating to flexible PVC and improve the water solubility of PVA resin; and using a small amount of acrylic-modified polyurethane (PUA) resin as a second modifying resin to improve the bonding force with flexible PVC and resist cracking caused by material deformation. This invention also adds a carboxylic acid-type propyl beet amphoteric surfactant to the coating, which has the dual effects of thickening and improving water washing residue, thereby accelerating the dissolution rate of the paint film during water washing. Therefore, the coating provided by this invention has excellent flexibility, is not prone to cracking, and has good water washing effect. However, this patent relates to the cleaning of flexible PVC, which is different from the application environment of coatings used on aluminum plates and PCB epoxy resin boards, and does not involve the flame retardant standard requirements of acrylic esters.
[0008] Invention patent CN2015105882116 discloses a water-washable anti-carburizing coating that can be removed after quenching. The coating is formulated from the following components in weight percentages: 25-35% boric acid, 15-25% filler, 15-25% aluminum dihydrogen phosphate, 1-5% coloring pigment, and 30-40% water. The invention also discloses a method for preparing the aforementioned water-washable anti-carburizing coating. This anti-carburizing coating can be removed by washing with water after carburizing heat treatment, thus solving the problem of traditional anti-carburizing coatings being difficult to peel off after carburizing heat treatment. The anti-carburizing coating formula uses inorganic high-temperature resistant materials as the anti-carburizing agent. The anti-carburizing agent, after being applied to the workpiece surface, forms an anti-carburizing coating with good adhesion and does not peel or flow at high temperatures, nor does it affect the carburizing atmosphere. This invention does not involve polyurethane resin as a film-forming agent.
[0009] Invention patent 201910576686.1 relates to an adhesive-coated aluminum-based cover plate for PCB drilling and its preparation method. The water-soluble composite polymer resin layer has moderate toughness, which guides the drill bit during its descent, thereby improving drilling accuracy. Simultaneously, the hot-melt resin within the water-soluble composite polymer resin layer lubricates the drill bit and cools it during drilling, effectively improving hole wall roughness, reducing wire entanglement, lowering drill bit temperature, and extending drill bit lifespan. Furthermore, the water-soluble composite polymer resin layer has good water solubility, making it easy to handle after drilling and less likely to adhere to PCB holes, thus ensuring drilling quality. The drawback of this resin is that it does not investigate whether the adhesive adhering to the PCB hole during drilling can be cleaned, and it does not emphasize the adhesion of the film formed by the drill bit being heated.
[0010] Invention patent 201310504176.6 involves the following steps: (1) preprocessing of the circuit board substrate, drilling through holes and copper plating, board surface electroplating, transfer of outer layer circuit patterns, pattern electroplating, etc.; (2) back drilling on PCB board 4, and checking whether the depth of the back drilled hole is qualified; (3) alkaline etching section and photosensitive solder resist after drilling the back drilled hole, and finally the finished product is obtained. The key points of its technical solution are: during back drilling, the drilling tape coefficient used in the drilling through hole process needs to be modified according to the expansion and contraction data that appears in the process of drilling through holes to drilling back drill holes on PCB board 4, so as to keep the drilling tape data consistent with the actual expansion and contraction; the drilling surface in the drilling through hole process is consistent with the drilling surface in the back drilling; a layer of phenolic pad 6 is added on the top of PCB board 4; which can effectively improve the depth accuracy and position accuracy of the back drilled hole of the existing PCB board 4, so as to ensure the integrity of the signal transmission of PCB board 4. This invention does not study the cleaning of the coating film and the adhesion of the drill bit film and the adhesion of fragments.
[0011] In summary, existing technologies have not comprehensively studied the combustion droplets, heat resistance (pkHHR, THR) of washable coatings coated on aluminum cover plates, the washability of the film on the aluminum cover plate, the hole position accuracy of the PCB core, the hole wall roughness and drill bit temperature, and the molten material in the hole diameter, etc. These indicators are key to evaluating the performance of washable coatings, so research on them is imperative. Summary of the Invention
[0012] The purpose of this invention is to address the problems encountered when drilling holes in PCB boards with coatings. These problems include coating melting, which affects drilling accuracy, and the resulting coating melting upon heating, leading to the adhesion of a sticky residue within the holes. This residue solidifies and is difficult to remove. To address these drawbacks, this invention designs a flame-retardant, washable, and moderately compatible water-based acrylic resin coating. Firstly, to address the issue of melting upon heating, the flame-retardant properties are improved to enhance the coating's performance. In the core layer, a char-forming intermediate is used in a free radical reaction with DOPO and 3,4-epoxy-1-butene to introduce these substances into the core layer. In acrylate monomer segments, both DOPO and p-hydroxybenzaldehyde possess rigid benzene ring groups, ensuring moderate surface strength during drilling. This prevents a decrease in precision due to high-speed drilling and avoids excessive small particles from breaking the resin film and splashing onto the PCB board, thus reducing the number of resin film particles on the PCB board. Secondly, the addition of 3,4-epoxy-1-butene prevents the resin film formed by DOPO and p-hydroxybenzaldehyde from becoming too hard and brittle. The use of porous carbon layer modifiers further contributes to this process. DOPO and 3,4-epoxy-1-butene participate in the shell radical reaction, introducing these substances into the acrylate resin chain segment and reducing the flammability of the acrylate resin; at the same time, gelatinized starch also enhances the melt resistance of PCB; furthermore, the partial hydroxyl groups of soluble starch react with the acyl chloride of benzoyl chloride, preventing excessive viscosity increase during subsequent gelatinization; ammonium persulfate is used as an initiator to initiate the free radical reaction of acrylamide, hexadecyl dimethyl allyl ammonium chloride, and N,N-methylenebisacrylamide. The solution reaction forms soluble acrylic resins. Then, under an alkaline environment, starch gelatinization is accelerated. The resulting gelatinized soluble starch has three functions: a) increasing the melting temperature of the acrylic resins; b) improving the water solubility of the acrylic resins; and c) increasing the swelling of the acrylic resins during heating and washing, allowing them to be quickly peeled from the epoxy resin PCB board, thus achieving appropriate compatibility with the PCB board. To address the water-related issues, hydrophilic acrylamide and hydroxyethyl acrylate are introduced into the shell layer to increase its washability.
[0013] A method for preparing flame-retardant, washable, and moderately compatible waterborne acrylic resin coatings, comprising the following steps:
[0014] (1) Preparation of core layer emulsion: Add 600-800g of water, 11-17g of emulsifier A, and 24-41g of methacrylic acid to the reaction vessel, mix and stir evenly, heat to 40-45℃, stir and react for 60min, add monomer A, 10.2-13.4g of char-forming intermediate, 18.3-21.6g of DOPO and 2.1-6.3g of 3,4-epoxy-1-butene, emulsify for 20-30min; heat to 65℃ and reflux water, heat to 80-90℃, add 10-12g of initiator dropwise for 1-1.5h, react for 1-2h, add 3.15-8.4g of diethanolamine, adjust pH to 8, react at 80-90℃ for 1-2h to obtain core layer emulsion;
[0015] (2) Add all monomer B and 8-12g of initiator dropwise to all the core layer emulsion obtained in step (1) for 1 hour, keep warm and stir at 75-85℃ for 1.5 hours, then add 4.6-5.5g of porous carbon layer modifier, 4.1-4.3g of DOPO, 1.2-2.4g of 3,4-epoxy-1-butene, 2.1g of initiator and 1.1-2.3g of starch modifier, react at 60-70℃ for 1 hour, cool down to 50℃, add 14-20g of emulsifier B, react for 30 minutes, add ammonia water to adjust the pH value to 7-8, and obtain the flame-retardant, washable, and moderately compatible waterborne acrylic resin coating.
[0016] The monomer A is composed of 40-55g of ethyl acrylate, 28-48g of methyl methacrylate, and 38-52g of hydroxyethyl acrylate.
[0017] The monomer B is a mixture of 49-69g of acrylamide, 12-54g of methyl methacrylate, and 55-92g of hydroxyethyl acrylate.
[0018] The emulsifier A is composed of sodium dodecylbenzenesulfonate and AEO-9 mixed in a mass ratio of 2:1;
[0019] The method for preparing the char-forming agent intermediate is as follows:
[0020] Add 6.1 g of p-hydroxybenzaldehyde to a beaker, dissolve it with 100–150 mL of ethanol, pour the solution into a 250 mL three-necked flask, stir at 250 r / min, heat to 50–60 °C, slowly add 1.5–1.8 g of ethylenediamine diluted in 10 mL of ethanol to the three-necked flask through a constant pressure dropping funnel, add the solution dropwise for 30 min, continue the reaction for 1–2.5 h, stop heating, cool to room temperature, filter, and obtain a pale yellow crude char-forming intermediate. Wash three times with ethanol, and dry under vacuum at 60 °C for 18–24 h to obtain a pale yellow char-forming intermediate powder, which is the char-forming agent intermediate.
[0021] The initiator is either ammonium persulfate or potassium persulfate;
[0022] The preparation method of porous carbon layer modified material is as follows:
[0023] (1) Cut vegetable tanned leather scraps into blocks with a length and width of 1 cm, place them in a vacuum tube furnace, and pre-carbonize them at 400°C for 3-4 h under a nitrogen atmosphere. Mix the resulting carbonized product with KOH at a mass ratio of 1:3. Then add 300% of the weight of water to the mixture and stir at 40-50°C for 18-22 h. Then dry the product and carbonize it again at 500-600°C for 1-2 h under nitrogen protection. Finally, dry it to obtain a porous carbon layer.
[0024] (2) 0.5 g of porous carbon layer, 4.5-6.7 g of pyrrole, 100 mL of water, and 0.4-0.6 g of sodium p-toluenesulfonate were stirred at 50-60 °C for 2-4 h. The product was dried, and then 50 mL of DMF and 8.17-11.2 g of erythritol were added to adjust the pH to 7.5. The mixture was stirred at 50-70 °C for 1-2 h. Then 27.4-36.4 g of phosphorus trichloride was added and the mixture was stirred at 30-40 °C for 1-2 h. Then 12.5-15.3 g of myristic acid was added and the mixture was stirred at 30-45 °C for 1-2 h. The resulting product was dried to obtain the porous carbon layer modified product.
[0025] The method for preparing the modified starch is as follows: Add 1-1.2g of benzoyl chloride and 15mL of benzene to 4g of soluble starch, stir and react at 30-40℃ for 30-40min, then rotary evaporate at 40-50℃ and dry to obtain the starch reactant; then add 20mL of deionized water at 70℃ to the starch reactant, stir for 30-40min, and add 0.03-0.05g of ammonium persulfate at 50-60℃ to obtain a pregelatinized soluble starch solution; then add 5.8g of acrylamide, 2.3g of hexadecyl dimethyl allyl ammonium chloride, and 2g of... The N,N-methylenebisacrylamide was mixed and dissolved in 10 mL of deionized water. Then, this solution was slowly poured into a pregelatinized soluble starch solution. The pH of the soluble starch solution was adjusted to 7.0 with 1 mol / L NaOH aqueous solution. The reaction was carried out for 15-30 min until the mixed solution became a gel. The mixture was stirred at 60-70°C for 2-3 h. The gel was then cut into small pieces with scissors and placed in an electric heating drying oven at 90°C for 2-3 h. Finally, it was dried for 24 h and pulverized through an 18-mesh sieve to obtain the modified starch.
[0026] The emulsifier B is AEO-9.
[0027] The positive effects of this invention are as follows:
[0028] (1) This invention constructs a core-shell flame-retardant, washable, and moderately compatible waterborne acrylate resin. The core layer uses relatively hard chain segments, while the shell layer uses soft chain segments. At higher temperatures, the film can quickly detach from the PCB board holes during cleaning. The core layer uses a char-forming intermediate and DOPO and 3,4-epoxy-1-butene for free radical reaction, introducing these substances into the acrylate monomer chain segments. Because DOPO and p-hydroxybenzaldehyde both have rigid benzene ring groups, their precision is not reduced due to high-speed drilling, and the resin film is not broken, preventing excessive small particles from splashing onto the PCB board, thus reducing PCB board defects. The number of resin film particles on the board; secondly, the addition of 3,4-epoxy-1-butene will not make the resin film formed by DOPO and p-hydroxybenzaldehyde too hard and cause it to crack. Moreover, at pH 8, 3,4-epoxy-1-butene is ring-opened, introducing diethanolamine with strong hydrophilicity. The -NH of diethanolamine is used to open the ring with epoxy in an alkaline environment. On the one hand, a nitrogen-containing element with flame retardant effect is introduced into the acrylate resin chain. On the other hand, the introduced hydroxyl groups not only enhance the hydrophilicity of the resin core layer, but also cause the hydroxyl groups to dehydrate and carbonize during the resin heating process, which enhances the resin's resistance to dripping and reduces the number of resin film particles on the PCB board and enhances its washability.
[0029] (2) This invention utilizes the aldehyde group of p-hydroxybenzaldehyde and the amino group of ethylenediamine to form a Schiff base through the condensation of the aldehyde group and the imino group. This reaction is easy to occur and generates an imine bond. Then, under the action of an initiator, the char-forming intermediate, DOPO and 3,4-epoxy-1-butene undergo a free radical reaction. The pH of DOPO reacts with C=N or C=C double bonds through an addition reaction to form a core layer. Ethylenediamine provides nitrogen element, which generates flammable gases such as nitrogen during combustion, causing the carbon layer to expand. p-hydroxybenzaldehyde and DOPO provide carbon source, forming a dense carbon layer covering the surface during combustion, which insulates heat and oxygen. The phosphorus element in DOPO captures oxygen free radicals released by combustibles, reducing the possibility of combustion, thereby achieving a flame retardant effect.
[0030] (3) In this invention, vegetable tanned leather scraps are carbonized in a nitrogen atmosphere to isolate oxygen. KOH is used to increase their fluffiness and carbonization is continued to obtain a porous carbon layer. Pyrrole is dispersed in the porous carbon layer. The phase change material erythritol reacts with the NH bond of pyrrole. The excess hydroxyl groups react with phosphorus trichloride. The excess phosphorus chloride bonds react with myristic acid, which has a phase change, to introduce a large amount of phase change material into the porous carbon layer. When the material is heated, it can absorb some heat and delay the possibility of combustion. At the same time, the large amount of carbon in the porous carbon layer reduces the possibility of combustion. The porous carbon layer modifier, DOPO and 3,4-epoxy-1-butene participate in the shell free radical reaction to introduce the above substances into the acrylic resin chain segment, thereby reducing the flammability of the acrylic resin.
[0031] (4) This invention utilizes the partial reaction of hydroxyl groups of soluble starch with the acyl chloride of benzoyl chloride to prevent excessive viscosity increase during subsequent gelatinization; then gelatinizes in water, utilizing the hydroxyl groups in the remaining starch to react with amino or imino groups, using ammonium persulfate as an initiator, and reacts acrylamide, hexadecyl dimethyl allyl ammonium chloride and N,N-methylenebisacrylamide in a free radical solution to form soluble acrylate resin. Then, under an alkaline environment, the starch gelatinization is accelerated. The resulting gelatinized soluble starch has three functions: a) increasing the melting temperature of acrylate resin; b) improving the water solubility of acrylate resin; c) increasing the swelling of acrylate resin during heating and washing, allowing it to be quickly peeled off from the epoxy resin PCB board, thus achieving appropriate compatibility with the PCB board. Detailed Implementation
[0032] Example 1
[0033] A method for preparing flame-retardant, washable, and moderately compatible waterborne acrylic resin coatings, comprising the following steps:
[0034] (1) Preparation of core layer emulsion: Add 600g of water, 11g of emulsifier A (made by mixing sodium dodecylbenzenesulfonate and AEO-9 in a mass ratio of 2:1) and 24g of methacrylic acid to the reaction vessel, mix and stir evenly, heat to 40℃, stir and react for 60min, add monomer A, 10.2g of char-forming intermediate, 18.3g of DOPO and 2.1g of 3,4-epoxy-1-butene, emulsify for 20min; heat to 65℃ and reflux water, heat to 80℃, add 10g of ammonium persulfate initiator (dissolved in 50g of water) dropwise, add dropwise for 1h, react for 1h, add diethanolamine 3.15g, adjust pH to 8, react at 80℃ for 1h to obtain core layer emulsion;
[0035] (2) Add all monomer B and 8g of ammonium persulfate initiator (dissolved in 40g of water) dropwise to all the core layer emulsion obtained in step (1) for 1 hour. Keep the mixture at 75°C and stir for 1.5 hours. Then add 4.6g of porous carbon layer modifier, 4.1g of DOPO, 1.2g of 3,4-epoxy-1-butene, 2.1g of ammonium persulfate initiator (dissolved in 4g of water) and 1.1g of starch modifier. React at 60°C for 1 hour. Cool down to 50°C and add 14g of emulsifier B (AEO-9). React for 30 minutes. Add ammonia water to adjust the pH value to 7-8 to obtain the flame-retardant, washable, and moderately compatible waterborne acrylic resin coating.
[0036] The monomer A is composed of 40g of ethyl acrylate, 28g of methyl methacrylate and 38g of hydroxyethyl acrylate;
[0037] The monomer B is a mixture of 49g acrylamide, 12g methyl methacrylate, and 55g hydroxyethyl acrylate.
[0038] The method for preparing the char-forming agent intermediate is as follows:
[0039] 6.1 g of p-hydroxybenzaldehyde was added to a beaker and dissolved in 100 mL of ethanol by stirring. The solution was then poured into a 250 mL three-necked flask and stirred at 250 rpm. The temperature was raised to 50 °C, and 1.5 g of ethylenediamine diluted in 10 mL of ethanol was slowly added dropwise to the three-necked flask through a constant pressure dropping funnel over a period of 30 min. The reaction was continued for 1 h, then heating was stopped, and the mixture was cooled to room temperature. The mixture was filtered to obtain a pale yellow crude char-forming intermediate. The intermediate was washed three times with ethanol and dried under vacuum at 60 °C for 18 h to obtain a pale yellow char-forming intermediate powder, which served as the char-forming agent intermediate.
[0040] The preparation method of porous carbon layer modified material is as follows:
[0041] (1) Cut vegetable tanned leather scraps into blocks with a length and width of 1 cm, place them in a vacuum tube furnace, and pre-carbonize them at 400°C for 3 h under a nitrogen atmosphere. Mix the resulting carbonized product with KOH at a mass ratio of 1:3. Then add 300% of the sample weight of water to the mixture and stir at 40°C for 18 h. Then dry the product and carbonize it again at 500°C for 1 h under nitrogen protection. Finally, dry it to obtain a porous carbon layer.
[0042] (2) 0.5 g of porous carbon layer, 4.5 g of pyrrole, 100 mL of water and 0.46 g of sodium p-toluenesulfonate were stirred at 50 °C for 2 h. The product was dried, and then 50 mL of DMF and 8.17 g of erythritol were added to adjust the pH to 7.5. The mixture was stirred at 50 °C for 1 h. Then 27.4 g of phosphorus trichloride was added and the mixture was stirred at 30 °C for 1 h. Then 12.5 g of myristic acid was added and the mixture was stirred at 30 °C for 1 h. The resulting product was dried to obtain the porous carbon layer modified product.
[0043] The method for preparing the modified starch is as follows: Add 1g of benzoyl chloride and 15mL of benzene to 4g of soluble starch, stir and react at 30℃ for 30min, evaporate by rotary evaporation at 40℃, and dry to obtain the starch reactant; then add 20mL of 70℃ deionized water to the starch reactant, stir for 30min, and add 0.03g of ammonium persulfate at 50℃ to obtain a pregelatinized soluble starch solution; then add 5.8g of acrylamide, 2.3g of hexadecyl dimethyl allyl ammonium chloride, and 2g of N,N-methylenedimethylamine (NDM) to the modified starch. Mix bisacrylamide and dissolve it in 10 mL of deionized water. Then slowly pour this solution into a pregelatinized soluble starch solution. Adjust the pH of the soluble starch solution to 7.0 with 1 mol / L NaOH aqueous solution. React for 15 min until the mixed solution becomes a gel. Stir and maintain at 60°C for 2 h. Then cut the gel into small pieces with scissors and place it in an electric heating drying oven at 90°C for 2 h. Finally, take it out and dry it for 24 h. Grind it and pass it through an 18-mesh sieve to obtain the starch-modified product.
[0044] Example 2
[0045] A method for preparing flame-retardant, washable, and moderately compatible waterborne acrylic resin coatings, comprising the following steps:
[0046] (1) Preparation of core layer emulsion: Add 800g of water, 17g of emulsifier A (made by mixing sodium dodecylbenzenesulfonate and AEO-9 in a mass ratio of 2:1) and 41g of methacrylic acid to the reaction vessel, mix and stir evenly, heat to 45℃, stir and react for 60min, add monomer A, 13.4g of char-forming intermediate, 1.6g of DOPO2 and 6.3g of 3,4-epoxy-1-butene, emulsify for 30min; heat to 65℃ and reflux water, heat to 90℃, add 12g of potassium persulfate initiator (dissolved in 30g of water) dropwise, add dropwise for 1.5h, react for 2h, add 8.4g of diethanolamine, adjust pH to 8, react at 90℃ for 2h to obtain core layer emulsion;
[0047] (2) Add all monomer B and 12g of potassium persulfate initiator (dissolved in 30g water) dropwise to all the core layer emulsion obtained in step (1) for 1 hour. Keep the mixture at 85°C and stir for 1.5 hours. Then add 5.5g of porous carbon layer modifier, 4.3g of DOPO, 2.4g of 3,4-epoxy-1-butene, 2.1g of potassium persulfate initiator (dissolved in 10g water) and 2.3g of starch modifier. React at 70°C for 1 hour. Cool down to 50°C and add 17g of emulsifier B (AEO-9). React for 30 minutes. Add ammonia water to adjust the pH value to 7-8 to obtain the flame-retardant, washable, and moderately compatible waterborne acrylic resin coating.
[0048] The monomer A is composed of 55g of ethyl acrylate, 48g of methyl methacrylate, and 52g of hydroxyethyl acrylate.
[0049] The monomer B is a mixture of 69g acrylamide, 54g methyl methacrylate, and 92g hydroxyethyl acrylate.
[0050] The method for preparing the char-forming agent intermediate is as follows:
[0051] 6.1 g of p-hydroxybenzaldehyde was added to a beaker and dissolved in 150 mL of ethanol by stirring. The solution was then poured into a 250 mL three-necked flask and stirred at 250 r / min. The temperature was raised to 60 °C. 1.8 g of ethylenediamine diluted in 10 mL of ethanol was slowly added dropwise to the three-necked flask through a constant pressure dropping funnel. The addition was carried out for 30 min, and the reaction was continued for 2.5 h. Heating was stopped, and the mixture was cooled to room temperature. The mixture was then filtered to obtain a pale yellow crude char-forming intermediate. The intermediate was washed three times with ethanol and dried under vacuum at 60 °C for 24 h to obtain a pale yellow char-forming intermediate powder, which is the char-forming agent intermediate.
[0052] The preparation method of porous carbon layer modified material is as follows:
[0053] (1) Cut vegetable tanned leather scraps into blocks with a length and width of 1 cm, place them in a vacuum tube furnace, heat at 400°C for 4 h under nitrogen atmosphere for pre-carbonization, mix the resulting carbonized product with KOH at a mass ratio of 1:3, then add 300% of the weight of water to the above mixture, stir at 50°C for 22 h, then dry the product, carbonize again at 600°C for 2 h under nitrogen protection, and finally dry it to obtain a porous carbon layer;
[0054] (2) 0.5g of porous carbon layer, 6.7g of pyrrole, 100mL of water and 0.6g of sodium p-toluenesulfonate were stirred at 60℃ for 4h. The product was dried, and then 50mL of DMF and 11.2g of erythritol were added to adjust the pH to 7.5. The mixture was stirred at 70℃ for 2h. Then 36.4g of phosphorus trichloride was added and the mixture was stirred at 40℃ for 2h. Then 15.3g of myristic acid was added and the mixture was stirred at 45℃ for 2h. The resulting product was dried to obtain the porous carbon layer modified product.
[0055] The method for preparing the modified starch is as follows: Add 1.2g of benzoyl chloride and 15mL of benzene to 4g of soluble starch, stir and react at 40℃ for 40min, then rotary evaporate at 50℃ and dry to obtain the starch reactant; then add 20mL of deionized water at 70℃ to the starch reactant, stir for 40min, and add 0.05g of ammonium persulfate at 60℃ to obtain a pregelatinized soluble starch solution; simultaneously, add 5.8g of acrylamide, 2.3g of hexadecyl dimethyl allyl ammonium chloride, and 2g of N,N- Mix methylenebisacrylamide and dissolve it in 10 mL of deionized water. Then slowly pour this solution into a pregelatinized soluble starch solution. Adjust the pH of the soluble starch solution to 7.0 with 1 mol / L NaOH aqueous solution. React for 30 min until the mixed solution becomes a gel. Stir and maintain at 70°C for 3 h. Then cut the gel into small pieces with scissors and place it in an electric heating drying oven at 90°C for 3 h. Finally, take it out and dry it for 24 h. Grind it and pass it through an 18-mesh sieve to obtain the modified starch.
[0056] Example 3
[0057] A method for preparing flame-retardant, washable, and moderately compatible waterborne acrylic resin coatings, comprising the following steps:
[0058] (1) Preparation of core layer emulsion: Add 700g of water, 14g of emulsifier A (made by mixing sodium dodecylbenzenesulfonate and AEO-9 in a mass ratio of 2:1) and 32.5g of methacrylic acid to the reaction vessel, mix and stir evenly, heat to 40℃, stir and react for 60min, add monomer A, 11.8g of char-forming intermediate, 20g of DOPO and 4.2g of 3,4-epoxy-1-butene, emulsify for 25min; heat to 65℃ and reflux water, heat to 85℃, add 11g of ammonium persulfate initiator (dissolved in 30g of water) dropwise, add dropwise for 1h, react for 1.5h, add 5.6g of diethanolamine, adjust pH to 8, react at 85℃ for 1.5h to obtain core layer emulsion;
[0059] (2) Add all monomers B and 10g of ammonium persulfate initiator (dissolved in 30g of water) dropwise to all the core layer emulsions obtained in step (1) for 1 hour. Keep the mixture at 80°C and stir for 1.5 hours. Then add 5g of porous carbon layer modifier, 4.2g of DOPO, 1.8g of 3,4-epoxy-1-butene, 2.1g of ammonium persulfate initiator (dissolved in 6g of water), and 1.7g of starch modifier. React at 65°C for 1 hour. Cool the mixture to 50°C and add 20g of AEO-9 emulsifier B. React for 30 minutes. Add ammonia water to adjust the pH value to 7-8 to obtain the flame-retardant, washable, and moderately compatible waterborne acrylic resin coating.
[0060] The monomer A is composed of 47.5g of ethyl acrylate, 38g of methyl methacrylate, and 45g of hydroxyethyl acrylate.
[0061] The monomer B is a mixture of 59g acrylamide, 38g methyl methacrylate, and 73.5g hydroxyethyl acrylate.
[0062] The method for preparing the char-forming agent intermediate is as follows:
[0063] 6.1 g of p-hydroxybenzaldehyde was added to a beaker and dissolved in 125 mL of ethanol by stirring. The solution was then poured into a 250 mL three-necked flask and stirred at 250 r / min. The temperature was raised to 55 °C. 1.65 g of ethylenediamine diluted in 10 mL of ethanol was slowly added dropwise to the three-necked flask through a constant pressure dropping funnel over a period of 30 min. The reaction was continued for 1.5 h, then heating was stopped, and the mixture was cooled to room temperature. The mixture was then filtered to obtain a pale yellow crude char-forming intermediate. The intermediate was washed three times with ethanol and dried under vacuum at 60 °C for 21 h to obtain a pale yellow char-forming intermediate powder, which is the char-forming agent intermediate.
[0064] The preparation method of porous carbon layer modified material is as follows:
[0065] (1) Cut vegetable tanned leather scraps into blocks with a length and width of 1 cm, place them in a vacuum tube furnace, and pre-carbonize them at 400°C for 3.5 h under a nitrogen atmosphere. Mix the resulting carbonized product with KOH at a mass ratio of 1:3. Then add 300% of the weight of water to the mixture and stir at 40-50°C for 20 h. Then dry the product and carbonize it again at 550°C for 1.5 h under nitrogen protection. Finally, dry it to obtain a porous carbon layer.
[0066] (2) 0.5 g of porous carbon layer, 5.6 g of pyrrole, 100 mL of water and 0.5 g of sodium p-toluenesulfonate were stirred at 55 °C for 3 h. The product was dried, and then 50 mL of DMF and 9.68 g of erythritol were added to adjust the pH to 7.5. The mixture was stirred at 60 °C for 1.5 h. Then 31.9 g of phosphorus trichloride was added and the mixture was stirred at 35 °C for 1.5 h. Then 13.9 g of myristic acid was added and the mixture was stirred at 40 °C for 1.5 h. The resulting product was dried to obtain the porous carbon layer modified product.
[0067] The method for preparing the modified starch is as follows: Add 1.1g of benzoyl chloride and 15mL of benzene to 4g of soluble starch, stir and react at 35℃ for 35min, evaporate by rotary evaporation at 45℃, and dry to obtain the starch reactant; then add 20mL of deionized water at 70℃ to the starch reactant, stir for 35min, and add 0.04g of ammonium persulfate at 55℃ to obtain a pregelatinized soluble starch solution; then add 5.8g of acrylamide, 2.3g of hexadecyl dimethyl allyl ammonium chloride, and 2g of N,N-methylenebis(methyl)-2-methyl ... Acrylamide mixture was added to 10 mL of deionized water and dissolved. This solution was then slowly poured into a pregelatinized soluble starch solution. The pH of the soluble starch solution was adjusted to 7.0 with 1 mol / L NaOH aqueous solution. The reaction was allowed to proceed for 22.5 min until the mixture became a gel. The mixture was stirred at 65 °C for 2.5 h. The gel was then cut into small pieces with scissors and placed in an electric heating drying oven at 90 °C for 2.5 h. Finally, the mixture was dried for 24 h and then pulverized through an 18-mesh sieve to obtain the modified starch product.
[0068] The prepared acrylic resin coating was poured into a polytetrafluoroethylene mold, with a thickness controlled at 3 mm, and then subjected to tests such as droplet testing and cone calorimetry.
[0069] Melting droplet test
[0070] (1) Sample preparation: The prepared acrylic resin film was placed in a constant temperature and humidity chamber set at 23℃±0.5℃ and 50%±5% for 48h. After that, it was taken out and cut into 110cm×10cm×3mm samples. Two sets of samples were prepared, with 5 samples in each set.
[0071] (2) Setting parameters: Clamp the sample about 5mm from the top so that it is vertically downward. Place a rosin board at the bottom of the sample, and pad the board with about 0.3g of degreased cotton. Place the sample evenly on the board. Adjust the gas flow rate to 105±5mL / min so that the flame height reaches 20±1mm. Set the ignition time to 10s.
[0072] (3) Flame recording: After setting the parameters, start the flame ignition. After 10 seconds of ignition, press the afterflame time start button. When the sample has finished burning and only sparks remain, press the afterflame combustion end button to enter the afterburn time. When the sample is completely extinguished, press the afterburn time end button to record the afterflame time and afterburn time.
[0073] (4) Observation of molten droplets: During the combustion process, observe whether molten droplets are produced during combustion, and whether the molten droplets falling onto the degreased cotton below will cause secondary combustion. Record the observation results.
[0074] The analysis was performed using ASTM E1354-1990 (2004 standard) and an FTT cone calorimeter 2000 (UK). The sample size was 10 cm × 10 cm, with a thickness of 3 mm, and the thermal radiation power was 12 kW / m². 2 The maximum heat release rate (kW / m) of pkHHR was determined. 2 Total heat released by THR (MJ / m³) 2 .
[0075] Take 28 parts of acrylate resin coatings, 0.2 parts of carboxymethyl cellulose, 4 parts of polyvinylpyrrolidone PVP-K30, 3 parts of polyvinyl alcohol, 6 parts of polyethylene glycol, and 1.5 parts of polyoxyethylene polypropylene ether from Examples 1 to 3, and add them to 35 parts of distilled water. Stir well, then add 2.5 parts of polypropylene glycol (PPG-400), 0.5 parts of leveling agent, and 0.6 parts of silane coupling agent. Stir well, filter, and let stand to defoam. Record this as the application plan.
[0076] The coating solutions from Examples 1 to 3 were sprayed onto epoxy resin circuit boards and dried at 70°C.
[0077] Wash with a 50℃ warm water solution for 30 minutes (temperature controlled at 50℃, KMnO4 50g / L, potassium manganate 10g / L, amplitude controlled at 20mm / s, sodium hydroxide 1mol / L, the remainder being water);
[0078] Its water washing test method: refer to the determination of the film removal time of the compound liquid coating by water washing [1] Xie Dan, Jia Danfeng. On water washable temporary protective coatings [J]. Synthetic Materials Aging and Application, 2017, 46(5): 43~50.
[0079] The PCB hole position accuracy was measured by sampling sections under a metallographic microscope, and the hole wall roughness was measured by a two-dimensional measuring instrument. The hole position accuracy, hole wall roughness, and hole diameter molten material were applied by spraying a coating (coating thickness 0.04mm) onto an aluminum foil (0.1mm) and then drilling on the lower PCB board.
[0080] The drill bit temperature was measured using a thermal infrared temperature detector;
[0081] The amount of molten material in the boreholes was determined by visual observation and comparison, and the results were categorized as few, relatively few, and many (for example, if fewer than 30 boreholes out of 100 boreholes contained molten material, it was defined as few; 31-70 boreholes contained relatively few; and 71-100 boreholes contained a lot).
[0082] The adhesion of the compounded solution to the coating film was determined according to GB / T 9286-1998 and ISO 2409:1992. For the soft substrate, epoxy resin board was used. 100 small squares of 1mm×1mm were cut on the coating sample with a blade and then bonded with transparent tape. The degree of damage to the paint film was observed to determine the adhesion grade of the paint film. The results were expressed as 0 to 5, with 0 being the worst and 5 being the best. Moderate compatibility was grade 2.
[0083] Table 1. Film properties of flame-retardant, washable, and moderately compatible waterborne acrylic resin coatings.
[0084] pkHHR 208.3 205.8 201.6 336.7 THR 33.4 31.6 32.8 92.5 Molten droplet condition Non-molten dripping Non-molten dripping Non-molten dripping Non-molten dripping Washability (50℃, s) 39 36 38 211 Hole position accuracy (mil) 1.6 1.8 1.5 2.6 Hole wall roughness (μm) 7 8 6 24 Drill bit temperature (°C) 75 82 89 102 Aperture melt few few few many Adhesion (Grade) 2 2 2 3
[0085] Using Example 2 of 202011318656.X as a comparative example, under the same conditions, equal amounts were substituted. Compared with the comparative example, the present invention has improvements in flame retardancy, washability, and compatibility. The PCB board in the example of the present invention has less molten material in the holes and is easier to clean. After the drill bit is heated, the film around the aluminum cover plate hardly sticks. In contrast, the comparative document shows that the film around the aluminum cover plate sticks after the drill bit is heated, and there is more molten material in the PCB board holes, which is more difficult to clean.
[0086] The following study was conducted using a comparative experiment based on Example 2.
[0087] Table 2 Properties of Flame-Retardant, Washable, and Moderately Compatible Waterborne Acrylic Resin Coatings
[0088]
[0089]
[0090] As shown in Table 2, the charring intermediate not only affects the flame retardancy (pkHHR, THR and droplet properties) of acrylate resin films, but also the drilling accuracy and hole roughness (drilling accuracy, hole roughness and hole melt when acrylate resin films are sprayed on aluminum cover plates and PCBs) and drill bit temperature. As shown in Table 2, the indicators without the addition of the charring intermediate are not as good as those with the addition of the above substances.
[0091] Table 3. Effects of porous carbon layer modification on flame retardancy, washability, moderate compatibility, and application properties of waterborne acrylic resins.
[0092]
[0093]
[0094] As shown in Table 3, porous carbon layer modifiers, phosphorus trichloride, myristic acid, and erythritol all improve the flame retardancy, pore accuracy, and pore wall roughness of acrylate resins.
[0095] Table 4. Effects of starch modification on flame retardancy, washability, moderate compatibility, and application properties of waterborne acrylic resins.
[0096]
[0097] Table 4 shows that the adhesion of the acrylic resin obtained without the above substances is not grade 2, the time required for water washability is increased, and the pore position accuracy and pore wall roughness are decreased. This indicates that starch modifier, benzoyl chloride, N,N-methylenebisacrylamide, and hexadecyldimethylallylammonium chloride play a significant role in improving the water washability and compatibility of acrylic resin coatings.
[0098] In addition, the pkHHR and THR of acrylate resin membranes without the addition of 3,4-epoxy-1-butene and diethanolamine increased, while the washability of the membranes without the addition of acrylamide and hydroxyethyl acrylate decreased.
Claims
1. A flame-retardant, washable, and moderately compatible water-based acrylic resin coating, characterized in that: The raw materials include char-forming agent intermediates, porous carbon layer modifiers, and starch modifiers; The method for preparing the char-forming agent intermediate is as follows: Add 6.1g of p-hydroxybenzaldehyde to a beaker, dissolve it with 100-150mL of ethanol, pour it into a 250mL three-necked flask, stir at 250r / min, heat to 50-60℃, slowly add 1.5-1.8g of ethylenediamine diluted with 10mL of ethanol to the three-necked flask through a constant pressure dropping funnel for 30min, continue the reaction for 1-2.5h, stop heating, cool to room temperature, filter, and obtain a pale yellow crude char-forming intermediate. Wash with ethanol 3 times, dry under vacuum at 60℃ for 18-24h to obtain a pale yellow char-forming intermediate powder, which is the char-forming agent intermediate; The method for preparing the porous carbon layer modified material is as follows: (1) Cut vegetable tanned leather scraps into blocks with a length and width of 1 cm, place them in a vacuum tube furnace, and pre-carbonize them at 400°C for 3-4 h under a nitrogen atmosphere. Mix the resulting carbonized product with KOH at a weight ratio of 1:3, then add 300% of the weight of water to the mixture and stir at 40-50°C for 18-22 h. Then dry the product and carbonize it at 500-600°C for 1-2 h under nitrogen protection. Finally, dry it to obtain a porous carbon layer. (2) 0.5g of porous carbon layer, 4.5-6.7g of pyrrole, 100mL of water, and 0.4-0.6g of sodium p-toluenesulfonate were stirred at 50-60℃ for 2-4h. The product was dried, and then 50mL of DMF and 8.17-11.2g of erythritol were added to adjust the pH to 7.
5. The mixture was stirred at 50-70℃ for 1-2h. Then 27.4-36.4g of phosphorus trichloride was added and the mixture was stirred at 30-40℃ for 1-2h. Then 12.5-15.3g of myristic acid was added and the mixture was stirred at 30-45℃ for 1-2h. The resulting product was dried to obtain the porous carbon layer modified product. The method for preparing the modified starch is as follows: Add 1-1.2g of benzoyl chloride and 15mL of benzene to 4g of soluble starch, stir and react at 30-40℃ for 30-40min, rotary evaporate at 40-50℃, and dry to obtain the starch reactant; then add 20mL of deionized water at 70℃ to the starch reactant, stir for 30-40min, and add 0.03-0.05g of ammonium persulfate at 50-60℃ to obtain a pregelatinized soluble starch solution; then add 5.8g of acrylamide, 2.3g of hexadecyl dimethyl allyl ammonium chloride, and 2g of N... Mix N-methylenebisacrylamide and dissolve it in 10 mL of deionized water. Then slowly pour this solution into a pregelatinized soluble starch solution. Adjust the pH of the solution to 7.0 with 1 mol / L NaOH and react for 15–30 min. The mixed solution will become a gel state. Stir and keep at 60–70 °C for 2–3 h. Then cut the gel into small pieces with scissors and place it in an electric heating drying oven at 90 °C for 2–3 h. Finally, take it out and dry it for 24 h. Grind it and pass it through an 18-mesh sieve to obtain the starch-modified product. The preparation method of flame-retardant, washable, and moderately compatible waterborne acrylic resin coatings is as follows: (1) Preparation of core layer emulsion: Add 600-800g of water, 11-17g of emulsifier A, and 24-41g of methacrylic acid to the reaction vessel, mix and stir evenly, heat to 40-45℃, stir and react for 60min, then add monomer A, 10.2-13.4g of char-forming intermediate, 18.3-21.6g of DOPO and 2.1-6.3g of 3,4-epoxy-1-butene, emulsify for 20-30min; heat to 65℃ and reflux water, heat to 80-90℃, add 10-12g of initiator dropwise for 1-1.5h, react for 1-2h, then add 3.15-8.4g of diethanolamine, adjust the pH to 8, and react at 80-90℃ for 1-2h to obtain core layer emulsion; (2) Add all monomer B and 8-12g of initiator dropwise to all the core layer emulsions obtained in step (1) for 1 hour. Keep the mixture at 75-85℃ and stir for 1.5 hours. Then add 4.6-5.5g of porous carbon layer modifier, 4.1-4.3g of DOPO, 1.2-2.4g of 3,4-epoxy-1-butene, 2.1g of initiator and 1.1-2.3g of starch modifier. React at 60-70℃ for 1 hour. Cool down to 50℃ and add 14-20g of emulsifier B. React for 30 minutes. Add ammonia to adjust the pH to 7-8 to obtain a flame-retardant, washable, and moderately compatible waterborne acrylic resin coating. The monomer A is composed of 40-55g of ethyl acrylate, 28-48g of methyl methacrylate, and 38-52g of hydroxyethyl acrylate. The monomer B is a mixture of 49-69g of acrylamide, 12-54g of methyl methacrylate, and 55-92g of hydroxyethyl acrylate.
2. The flame-retardant, washable, and moderately compatible waterborne acrylic resin coating as described in claim 1, characterized in that, The emulsifier A is composed of sodium dodecylbenzenesulfonate and AEO-9 mixed in a mass ratio of 2:
1.
3. The flame-retardant, washable, and moderately compatible waterborne acrylic resin coating as described in claim 1, characterized in that, The initiator is either ammonium persulfate or potassium persulfate.
4. The flame-retardant, washable, and moderately compatible waterborne acrylic resin coating as described in claim 1, characterized in that, The emulsifier B is AEO-9.
Citation Information
Patent Citations
A manufacturing method to improve the accuracy of back drilling on PCB boards
CN103533761B
Gluing aluminum-based cover plate for PCB drilling and preparing method thereof
CN110281308A
Preparation method of flame-retardant core-shell type environmentally friendly waterborne resin coating
CN112322132B
Washable temporary decorative coating for soft PVC (polyvinyl chloride) as well as preparation method and application of washable temporary decorative coating
CN114921135A
Preparation method of flame-retardant and antibacterial waterborne core-shell acrylate resin paint and oil paint
CN108912929A